Understanding online second-hand consumption among young consumers: A theory of planned behavior perspective - Minh, Nguyen Tien; Kien, Nguyen The; Ha, Truong Thu; Lich, Hoang Khac; Anh, Nguyen Thi Minh (Edelweiss Applied Science and Technology, 2026)
This study advances understanding of online second-hand consumption among young consumers by examining the Theory of Planned Behavior (TPB) in a digital platform context within an emerging economy, specifically Vietnam. The research aims to explore how attitudes, subjective norms, perceived behavioral control, and perceived economic benefits jointly influence purchase intention and actual behavior. Data were collected from young Vietnamese consumers with prior experience in online second-hand shopping. Partial Least Squares Structural Equation Modeling was employed to evaluate the research model and test the hypothesized relationships. The findings reveal that perceived economic benefits and perceived behavioral control play a dominant role in shaping both intention and behavior, while subjective norms exert a modest influence on intention. Environmental concern shows a weak association with attitudes and does not translate into purchase intention. Notably, attitudes display limited explanatory power for intention, whereas intention strongly predicts actual purchasing behavior, highlighting an attitude-behavior gap in online second-hand consumption. Consequently, the study offers theoretical insights into how economic value and behavioral feasibility condition sustainable consumption decisions among young consumers. It also provides practical implications for e-commerce platforms to design targeted marketing strategies that emphasize cost-efficiency, shopping convenience, and social approval to foster sustainable consumption.